Link Selection Schemes For Cooperative Buffer-Aided Relay Networks - Siddig, Ali Ahmed Mohamed (2018)
Recently, cooperative buffer-aided relaying technique has emerged. In which, the flexibility offered by the buffering capability is exploited to improve the performance in many aspects such as capacity, diversity gain and power consumption. However, the improvement comes at the price of higher transmission delay. In this thesis, the objectives are to develop the cooperative relaying systems with and without delay constraints as well as to determine an optimal link selection scheme that maximizes the throughput of cooperative relaying systems with simultaneous wireless information and power transfer (SWIPT). First, for cooperative relaying systems without delay constraints, a new link selection scheme that minimizes the outage probability is proposed. It exploits the channel state information (CSI) and buffer state information (BSI) to maintain the states of the buffers, thereby minimizing the outage probability. The outage probability performances in independent and identically distributed (i.i.d.) and independent and non-identically distributed (i.n.d.) Rayleigh fading channels are investigated. As compared to the buffer-state-based (BSB) scheme that offers the minimum outage probability among previous schemes, simulation results show that the proposed scheme offers lower outage probability and can achieve the BSB scheme’s performance using less transmission power. In the three-node network, the offered reduction in power has reached 2.5 dBW at some power values (e.g., using 17 dBW instead of 19.5 dBW). For real-time cooperative relaying systems with specific information rates and delay constraints, a new link selection scheme is proposed. The proposed scheme exploits the CSI, BSI and delay state information (DSI) to minimize the outage and packet dropping probabilities and achieve higher throughput. In order to achieve that, it uses these information to compromise between the selections of relays for reception and transmission. The proposed scheme is analysed in the i.i.d. and i.n.d. Rayleigh fading channels. For systems with high delay constraints, simulation results show that the proposed scheme offers lower packet dropping probability and higher throughput as compared to the renowned relay selection schemes. The proposed scheme offers reduction in power that exceeds 1 dBW in some simulations. Lastly, SWIPT in cooperative buffer-aided relaying systems is investigated. Power splitting (PS) technique is considered for SWIPT implementation. An optimal link selection scheme that maximizes the system throughput is proposed. In each time slot, an optimal PS ratio is employed if the source is chosen for transmission, while the relay transmits with optimal power if selected. As compared to the conventional schemes that use predefined transmission schedule, simulation results show that the proposed scheme offers higher throughput and signal-to-ratio (SNR) gain that exceeds 10 dB at some SNR regions.